Current Status of Human Adipose–Derived Stem Cells: Differentiation into Hepatocyte-Like Cells. (16th August 2011) - Al Battah, Feras; De Kock, Joery; Vanhaecke, Tamara; Rogiers, Vera
Abstract : The shortage of human organ donors and the low cell quality of available liver tissues represent major obstacles for the clinical application of orthotropic liver transplantation and hepatocyte transplantation, respectively. Therefore, worldwide research groups are investigating alternative extrahepatic cell sources. Recent in vitro studies have demonstrated that mesenchymal stem cells (MSCs) from various sources, including human bone marrow, adipose tissue, and umbilical cord, can be differentiated into hepatocyte-like cells when appropriate conditions are used. In particular, interest exists for human adipose–derived stems cells (hASCs) as an attractive cell source for generating hepatocyte-like cells. The hASCs are multipotent MSCs that reside in adipose tissue, with the ability to self-renew and differentiate into multiple cell lineages. Moreover, these cells can secrete multiple growth factors and cytokines that exert beneficial effects on organ or tissue injury. In this review, we will not only present recent data regarding hASC biology, their isolation, and differentiation capability towards hepatocytes, but also the potential application of hASC-derived hepatocytes to study drug toxicity. Additionally, this review will discuss the therapeutic potential of hASCs as undifferentiated cells in liver regeneration.